1988
DOI: 10.1083/jcb.107.6.2117
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of exocytosis in human neutrophils.

Abstract: Abstract. We have investigated the dynamics of exocytosis in single human neutrophils. The increase of membrane area associated with granule fusion was followed by time-resolved patch-clamp capacitance measurements. Intracellular application of 20 ~tM guanosine-5'-O(3-thiotriphosphate) (GTP~,S) in the presence of 2.5 mM ATP stimulated exocytosis and led to an increase of membrane capacitance from 3.0 to ,,~8.4 pF corresponding to a 540 ~tm 2 increase of membrane area. This capacitance change is very close to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 27 publications
(34 reference statements)
3
53
1
Order By: Relevance
“…Highly Ca 2ϩ -buffered pipette solutions with different Ca 2ϩ concentrations ([Ca 2ϩ ] p ) were dialyzed against the cytosol in standard whole-cell patch-clamp mode. to 76 SLs, assuming an average diameter of 500 nm (17), and a specific C m as 10 fF͞ m (2, 18), whereas for mast cells and neutrophils, the estimated granule number is Ͼ1,000 (15,16,19). It is unclear whether the preformed SLs are sufficient or the de novo formation of SLs is necessary for their lytic function.…”
Section: Resultsmentioning
confidence: 99%
“…Highly Ca 2ϩ -buffered pipette solutions with different Ca 2ϩ concentrations ([Ca 2ϩ ] p ) were dialyzed against the cytosol in standard whole-cell patch-clamp mode. to 76 SLs, assuming an average diameter of 500 nm (17), and a specific C m as 10 fF͞ m (2, 18), whereas for mast cells and neutrophils, the estimated granule number is Ͼ1,000 (15,16,19). It is unclear whether the preformed SLs are sufficient or the de novo formation of SLs is necessary for their lytic function.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, we observed that amantadine inhibited clathrin reorganization into clathrin-coated pits with subsequent decrease in dual phosphorylation (activation) of p38 MAPK. Many of the cellular responses elicited by PAF are directly influenced by p38 MAPK activation, priming of the respiratory burst, and actin reorganization; however, the effects on intracellular granules, whether due to the specific granules binding to the membrane and increasing the surface expression of CD11b or to the release of proteases from azurophilic granules, is not as well understood and have been proposed to involve multiple mechanisms including MAPKs and changes in cytosolic Ca 2ϩ (18,44,45). Importantly, amantadine does inhibit the PAFinduced activation of p38 MAP kinase but did not affect the PAF-mediated increases in cytosolic Ca 2ϩ , which may be the reason that amantadine only attenuates the PAF-elicited changes in PMN physiology related to the movement or release of granule constituents including both the release of elastase and the increased surface expression of CD11b (7,42,69).…”
Section: Discussionmentioning
confidence: 99%
“…180 Primary granules (also known as azurophilic granules) are positive for myeloperoxidase and, therefore, have a critical role in the potentiation of the respiratory burst. 211 Furthermore, these granules contain a bevy of antimicrobial compounds such as defensins, lysozyme, and bactericidal/permeability-increasing protein and three serine proteases: cathepsin G, neutrophil elastase, and proteinase 3. 212 These are the first granules formed during PMN differentiation.…”
Section: Degranulationmentioning
confidence: 99%